PENGARUH STRATEGI PEMBELAJARAN NUMBERED HEADS TOGETHER (NHT) TERHADAP HASIL BELAJAR SISWA SMA NEGERI 1 MUARA BADAK - Nursyamsi SY; Aloysius Duran Corebima; Herawati Susilo (Graduate School of Universitas Negeri Malang, 2016)
This research aims at investigating the effect of NHT learning strategy on students’ learning outcomes. This is quasi experimental research. The design of this research was Pretest-Posttest Non-equivalent Control Design. The population of this research was all the students of class XI of public senior high school students in Muara Badak in the first semester of 2015/2016 academic year. The samples of this research were the students of class XI natural science 1 and XI natural science 2. There were 30 students in each of the class. The data were obtained from essay tests. The data were analyzed using Ancova. The results of the analysis showed that the learning strategy had an effect on the learning outcomes. It was observed from the comparison of the mean corrected score that the NHT learning strategy had a more significant effect as much as 21,56%, compared to the effect from the conventional learning.Penelitian ini bertujuan untuk mengetahui pengaruh strategi pembelajaran Numbered Head Together terhadap hasil belajar siswa. Jenis penelitian ini adalah quasy eksperimen. Desain penelitian yang digunakan adalah Pretest-Postest Non-equivalent Control Design. Populasi penelitian ini seluruh siswa kelas XI SMAN 1 di Muara Badak pada semester ganjil tahun pelajaran 2015/2016. Sampel penelitian ini adalah siswa kelas XI IPA 1 dan XI IPA 2. Dua kelas yang digunakan masing-masing berjumlah 30 siswa. Data diperoleh dari hasil belajar kognitif. Data penelitian ini dianalisis menggunakan Anakova. Berdasarkan hasil analisis menunjukkan bahwa strategi pembelajaran memberikan pengaruh terhadap hasil belajar kognitif siswa. Hal ini dilihat dari perbandingan rerata terkoreksi diketahui bahwa strategi pembelajaran NHT memberikan pengaruh lebih besar, yaitu sebesar 21,56%, dibandingkan pengaruh yang disebabkan oleh pembelajaran konvensional.